Variable phenotypic presentation of a novel FOXF1 missense mutation in a single family. Issue 9 (4th May 2016) - Reiter, Joel; Szafranski, Przemyslaw; Breuer, Oded; Perles, Zeev; Dagan, Tamir; Stankiewicz, Paweł; Kerem, Eitan
Summary: Background: Heterozygous mutations in the FOXF1 transcription factor gene are implicated in alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV), a developmental disorder of the lungs classically presenting with pulmonary hypertension and early demise. Evidence has suggested haploinsufficiency and partial paternal imprinting. We present a family with several affected members with an extremely variable phenotype. Patients: The index patient presented several hours after birth with severe pulmonary hypertension. She is now 3‐years old, thriving on maximal pulmonary hypertension therapy, chronic steroids, and oxygen. One of the patient's siblings died at 16 days with pulmonary hypertension and an annular pancreas, consistent with classical ACDMPV. Methods: Whole exome sequencing was performed in the index case. The identified variant was confirmed by Sanger sequencing, and tested in the remaining family members. Parental origin was determined by PCR amplification and cloning, sequencing, and identification of adjacent single nucleotide polymorphisms. Echocardiography was performed in the asymptomatic carriers. Results: Whole exome analysis revealed a novel, predictably pathogenic heterozygous missense mutation, g.chr16:86544406 C>A NM_001451, c.C231A, p.F77L, in the FOXF1 gene. The mutation arose in the father, de novo, early postzygotically, with 70% somatic mosaicism in the blood, on the grandpaternal chromosome. It was also present in the proband's asymptomatic sister, found to have partial anomalous pulmonary venous return. Conclusion: FOXF1 mutations may have an extremely variable phenotype, possibly as a result of somatic mosaicism and complex gene regulation including unorthodox imprinting of the gene locus. The prolonged survival of the proband suggests the need for aggressive treatment.Pediatr Pulmonol. 2016; 51:921–927 . © 2016 Wiley Periodicals, Inc.